2003
DOI: 10.1108/00251740310509580
|View full text |Cite
|
Sign up to set email alerts
|

The special challenges of academic leadership

Abstract: The special challenges of academic leadership Management Decision 41/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 2 publications
0
97
0
1
Order By: Relevance
“…The HOD is also required to provide leadership for both academic and administrative functions. In contrast to the middle managers in administrative departments, some academics find themselves in management roles which they did not necessarily aspire to but that are required in the university management context (Rowley and Sherman 2003). In other cases, academics deliberately want to move away from teaching and research by taking on a management role as the current concept of an academic career is very different from the one of two decades earlier (Deem 2004).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The HOD is also required to provide leadership for both academic and administrative functions. In contrast to the middle managers in administrative departments, some academics find themselves in management roles which they did not necessarily aspire to but that are required in the university management context (Rowley and Sherman 2003). In other cases, academics deliberately want to move away from teaching and research by taking on a management role as the current concept of an academic career is very different from the one of two decades earlier (Deem 2004).…”
Section: Introductionmentioning
confidence: 98%
“…A thematic search across a wide range of publications in the last 15 years has revealed that reporting on middle managers in higher education in developed countries is not new. Our thematic search, using middle managers and universities as search criteria, identified studies by Burnes, Wend, and By (2013), Schneijderberg and Merkator (2013), Rayner et al (2010), Whitchurch (2008), Bryman (2007, Deem (2004), Parker (2004, Rowley and Sherman (2003) and Wolverton, Ackerman, and Holt (2005). The focus of these identified studies was on academic managers.…”
Section: Introductionmentioning
confidence: 99%
“…In The Special Challenges of Academic Leadership, Rowley & Sherman (2003) posit that, "leadership is an essential ingredient of positions with supervisory responsibilities in any organization" (p. 1058). While this sentiment indeed is sincere, it is important to define leadership to understand why it is indispensable to organizational success.…”
Section: Leadership Management or Both?mentioning
confidence: 99%
“…Therefore, the successful development of effective leadership is critical for both performance and accomplishment. This is not just true of commercial organizations, but also of academic agencies (Bensimon & Neumann, 1992;Braun, Nazlic, Weisweiler, Pawlowska, Peus, & Frey, 2009;Rowley & Sherman, 2003). Arsenault (2007) states, "Universities are definitely not immune to this need for effective leadership as they face similar challenges as any other organizations" (p. 14).…”
mentioning
confidence: 99%
See 1 more Smart Citation